An Experimental Investigation on the Effect of Fin in the Performance of Closed Loop Pulsating Heat Pipe (CLPHP). (2015) - Rahman, M. Lutfor; Sultan, Rasel A.; Islam, T.; Hasan, Noor M.; Ali, Mohammad
Abstract: Pulsating heat pipes (PHP) have created a newer arena and promising possibilities as passive devices for heat transfer applications, especially suited for thermal management of electronics. A closed loop pulsating heat pipe (CLPHP) made of copper with 2 mm ID and 2.5 mm OD with fin in the condenser section is used in the present work to evaluate the heat transfer performances where the evaporation section is 50 mm, adiabatic section is 120 mm and condensation section is 80 mm. The attempt is to analyze and compare the effects on the heat transfer performances of CLPHP with finned and un-finned condenser section with inclination angle of 0° (vertical), 30° and 45°. Methanol is used as working fluid with 50% filling ratio in CLPHP with 8 loops during the experimentation. The experimental results indicate a strong influence of gravity and thermo physical properties of the working fluid on the performance of the CLPHP studied with different orientation and heat load. The results demonstrate the effect of fin used in condenser section, the input heat flux, inclination angle orientation and physiochemical properties of the working fluid on the thermal performance of the device. The finned CLPHP at 45° inclination exhibits the considerable enhancement of heat transfer compared with that of CLPHP without fin.